2021
DOI: 10.3389/fphys.2021.721775
|View full text |Cite
|
Sign up to set email alerts
|

TGF-Beta Receptor II Is Critical for Osteogenic Progenitor Cell Proliferation and Differentiation During Postnatal Alveolar Bone Formation

Abstract: Transforming growth factor beta (TGFβ) signaling plays an important role during osteogenesis. However, most research in this area focuses on cortical and trabecular bone, whereas alveolar bone is largely overlooked. To address the role of TGFβR2 (the key receptor for TGFβ signaling) during postnatal alveolar bone development, we conditionally deleted Tgfβr2 in early mesenchymal progenitors by crossing Gli1-CreERT2; Tgfβr2flox/flox; R26RtdTomato mice (named early cKO) or in osteoblasts by crossing 3.2kb Col1-Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…In mice with conditional deletion of TGFb R2 (a major receptor for TGFb signaling) from early mesenchymal progenitor cells, alveolar bone mass and density were significantly reduced during early development and the periodontal ligament was severely damaged (Xu et al, 2021). Bone morphogenetic proteins (BMPs) belong to the TGF-b family, which is a group of highly conserved and structurally similar functional proteins.…”
Section: Tgf-b Signalingmentioning
confidence: 99%
“…In mice with conditional deletion of TGFb R2 (a major receptor for TGFb signaling) from early mesenchymal progenitor cells, alveolar bone mass and density were significantly reduced during early development and the periodontal ligament was severely damaged (Xu et al, 2021). Bone morphogenetic proteins (BMPs) belong to the TGF-b family, which is a group of highly conserved and structurally similar functional proteins.…”
Section: Tgf-b Signalingmentioning
confidence: 99%
“…It has previously justified that TGF-β could regulate osteogenesis of periodontal ligament fibroblasts [ 30 ]. Previous study also demonstrated the essential role of TGFβR2 in osteogenic periodontal ligament cells during early alveolar bone development, and deletion of TGFβR2 in osteogenic progenitor cells resulted in significant alveolar bone loss [ 14 ]. Our results showed that miR‐223 directly binds to the 3′‐UTR of TGFβR2 mRNA, and silencing of TGFβR2 markedly inhibited PDL-derived cells osteogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…It has been demonstrated to play pivotal roles in osteoblast differentiation [ 13 ]. TGFβR2, a receptor of the transforming growth factor beta (TGF-β), is also a major regulator of osteogenesis and bone repair [ 14 ]. Additionally, members of the FGFs and TGFβ families are known to be essential for osteoblast differentiation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…TGFβ signaling has also been shown to drive the formation of tendon and the enthesis; loss of TGFβ signaling results in defective tendon and ligament formation [20, 21] and abnormal enthesis mineralization [49]. Furthermore, recent reports have suggested that TGFβ controls fibrocartilage and ligament cell proliferation [22, 50]. However, the molecular mechanisms by which TGFβ controls tendon and enthesis formation remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies revealed that TGFβ signaling was necessary to maintain tendon cell phenotype via Scx expression [21]. Recently, deletion of TbR2 in Gli1 expressing periodontal ligament (PDL) progenitors was shown to reduce PDL cell numbers [22]. These prior studies point to a crucial role for TGFβ in the formation of tendon and the mineralization of the tendon enthesis.…”
Section: Introductionmentioning
confidence: 99%